A Randomized, Double-blind, Placebo-controlled, Parallel-group, Pilot Study of Cannabidiol-rich Botanical Extract in the Symptomatic Treatment of Ulcerative Colitis. Issue 4 (10th March 2018) - Irving, Peter M; Iqbal, Tariq; Nwokolo, Chuka; Subramanian, Sreedhar; Bloom, Stuart; Prasad, Neeraj; Hart, Ailsa; Murray, Charles; Lindsay, James O; Taylor, Adam; Barron, Rachel; Wright, Stephen
Abstract: Background: Cannabidiol (CBD) exhibits anti-inflammatory properties that could improve disease activity in inflammatory bowel disease. This proof-of-concept study assessed efficacy, safety and tolerability of CBD-rich botanical extract in ulcerative colitis (UC) patients. Methods: Patients aged 18 years or older, with left-sided or extensive UC, Mayo scores of 4–10 (endoscopy scores ≥1), and on stable 5-aminosalicylic acid dosing, were randomized to 10-weeks' CBD-rich botanical extract or placebo capsules. The primary endpoint was the percentage of patients in remission after treatment. Statistical testing was 2-sided, using a 10% significance level. Results: Patients were less tolerant of CBD-rich botanical extract compared with placebo, taking on average one-third fewer capsules, and having more compliance-related protocol deviations (principally insufficient exposure), prompting identification of a per protocol (PP) analysis set. The primary endpoint was negative; end of treatment remission rates were similar for CBD-rich botanical extract (28%) and placebo (26%). However, PP analysis of total and partial Mayo scores favoured CBD-rich botanical extract ( P = 0.068 and P = 0.038, respectively). Additionally, PP analyses of the more subjective physician's global assessment of illness severity, subject global impression of change, and patient-reported quality-of-life outcomes were improved for patients taking CBD-rich botanical extract ( P = 0.069, P = 0.003, and P = 0.065, respectively). Adverse events (AEs) were predominantly mild/moderate with many in the CBD-rich botanical extract group potentially attributable to the ∆ 9 -tetrahydrocannabinol content. A greater proportion of gastrointestinal-related AEs, indicative of UC worsening, was seen on placebo. Conclusion: Although the primary endpoint was not reached, several signals suggest CBD-rich botanical extract may be beneficial for symptomatic treatment of UC.